JOURNEYING TO INDEPENDENCE AND AUTONOMY: TRANSITION NORMS AND EMPOWERING ADOLESCENTS WHO ARE DEAF AND HARD OF HEARING (Annual of the Faculty of Philosophy in Skopje, 2020)
When discussing transitions of deaf and hard of hearing adolescents, we have toperceive them holistically, and to recognize the nature and complexity of the relationshipsbetween traditional transitions. Measures of ‘successful’ or ‘unsuccessful’ transitions,do not necessarily align with the traditional events-based and institutional transitions.We need to broaden our understandings of transitionary processes and desirableoutcomes. Successful transition begins with trusting deaf and hard of hearing studentsto lead their own transition planning.Autonomy of deaf adolescents is linked to better employment with more opportunitiesfor advancement and higher income. Autonomous beliefs, capacities, and actionsare associated with improved outcomes for students with disabilities. When weare discussing employment opportunities, it is evident that there has been a shift of thetraditional parameters of the industrial society. The old traditional occupations arereplaced by the necessity for individuals to adapt to new standards of work and changinglabour market conditions, by for example, re-training or switching occupations. Tosupport development of autonomy, environments must facilitate opportunities for theindividual to take control over their own lives, to make choices and decisions freely.When we discuss independence and autonomy, we must also relate it to newand uprising technologies. Technology can mean increased access, independence, andreliance of oneself. With high expectations from parents and teachers and using technologyfor meaningful education, these deaf and hard of hearing adolescents will beready for college and careers.
Keywords: DEAF; ADOLESCENCE; AUTONOMY; INDEPENDENCE